SEKA -A CURTAIN RAISER TO OCULAR THERAPY IN THE MANAGEMENT OF INFLAMMATORY DISEASES OF EYE - Dhotre, *Darshana; K V, Mamatha; K, Sujathamma. (International Journal of Ayurveda and Pharma Research, 2016)
Kriyakalpa- Topical Ocular Therapeutic procedures enlisted under Bahirparimarjana Chikitsa are boon to treat Netra vikaras in present day practice as it carry the advantages such as the structures directly, crossing certain barriers providing more time for bio-availability. Acharya Sharangadhara has also highlighted Kriyakalpa and also gave a clinical order of application of these procedures. He opined that Netra Parisheka/Seka (closed eye irrigation), Ashchyotana (Eye drops), Pindi (Poultice application), Bidalaka (application of medicated paste on lids), these four are applied in Aamavastha (inflammatory stage), where as Tarpana (Satiation), Putapaka (retention of medicinal decoction along with Mamsa rasa), Anjana (Collyrium/eye ointment) are indicated in Nira amavastha (chronic stage) of Netra roga (Eye diseases). These are the seven procedures in order of their clinical application. The importance of Seka (irrigation) - local ocular therapeutic and its measures in eye care is immense in to the present day in any inflammatory conditions as acute management due to its vast advantages, cost effect, availability of the drugs and procedure. In this area of Presentation a brief overview on Seka, its variants, Indications, Clinical applications and rationality of the drugs used which are commonly available and Probable mode of action will be convened to increase the confident level and make more ease to practice Seka in different inflammatory conditions as an acute management to achieve success clinically.